Inhibition of the oncogenic channel Kv10.1 by the antipsychotic drug penfluridol - León-Sánchez, Paulina; Cedillo-Hernández, Andrea Lizeth; Durán-Pastén, María Luisa; Lara-Figueroa, Cesar Oliver; Hernández-Cruz, Arturo; Luis, Enoch (Frontiers in Pharmacology, 2025)
Drug repurposing is an increasingly recognized strategy in pharmaceutical development that focuses on identifying new therapeutic uses for already approved drugs, as an alternative to the time-consuming and costly process of developing new molecular entities. This approach has gained traction in oncology, especially in exploring the anticancer potential of non-oncologic agents. In recent years, the antipsychotic drug penfluridol (PNFL) has been identified as having antitumoral properties; however, the underlying mechanisms remain poorly understood. We hypothesized that PNFL may exert its effects by inhibiting the oncogenic potassium channel Kv10.1. Our results demonstrate that PNFL inhibits Kv10.1 activity and reduces cell migration in HEK-Kv10.1 cells. These findings suggest a novel mechanism that may contribute to the drug’s antitumoral effects.